Design of whey protein nanostructures for incorporation and release of nutraceutical compounds in food. Issue 7 (3rd May 2017) - Ramos, Oscar L.; Pereira, Ricardo N.; Martins, Artur; Rodrigues, Rui; Fuciños, Clara; Teixeira, José A.; Pastrana, Lorenzo; Malcata, F. Xavier; Vicente, António A.
ABSTRACT: Whey proteins are widely used as nutritional and functional ingredients in formulated foods because they are relatively inexpensive, generally recognized as safe (GRAS) ingredient, and possess important biological, physical, and chemical functionalities. Denaturation and aggregation behavior of these proteins is of particular relevance toward manufacture of novel nanostructures with a number of potential uses. When these processes are properly engineered and controlled, whey proteins may be formed into nanohydrogels, nanofibrils, or nanotubes and be used as carrier of bioactive compounds. This review intends to discuss the latest understandings of nanoscale phenomena of whey protein denaturation and aggregation that may contribute for the design of protein nanostructures. Whey protein aggregation and gelation pathways under different processing and environmental conditions such as microwave heating, high voltage, and moderate electrical fields, high pressure, temperature, pH, and ionic strength were critically assessed. Moreover, several potential applications of nanohydrogels, nanofibrils, and nanotubes for controlled release of nutraceutical compounds (e.g. probiotics, vitamins, antioxidants, and peptides) were also included. Controlling the size of protein networks at nanoscale through application of different processing and environmental conditions can open perspectives for development of nanostructures with new or improved functionalities for incorporation and release of nutraceuticals in food matrices.